Pendekatan STEAM (Science, Technologi, Art, And Math) Sebagai Perencanaan Pembelajaran PAUD - Wafa Aerin; Diana Ledy Ellizzah; M. Utsman Arif Fathah (Pusat Studi Pendidikan Kreatifitas Anak Wadas Kelir Purwokerto, 2021)
The writing of this paper aims to explain how to answer the challenges of advancing science and technology more rapidly by preparing students to go ahead and develop with 21st Century learning planning namely STEAM-based learning (Science, Technology, Eingeneering, Art and Mathematic). Learning planning is a design for teachers in carrying out play activities to facilitate children in the learning process. The lesson plan must refer to the characteristics (age, social culture, and needs of the individual). 21st Century Learning is learning that integrates the abilities of knowledge, skills and attitudes as well as mastery of technology. This research is a qualitative research. Data collection techniques used in the form of interviews, field observations and reflective journals. Planning becomes the most important part in a learning process, which focuses more on 4C (Communication, Collaborative, Creatical Thingking, and Creativity). STEAM-based learning (Science, Technology, Eingeneering, Art and Mathematic) will help train children to be able to analyze existing problems using a variety of approaches, both science, technology, engineering, arts and mathematics so that it becomes a step for the survival of students in wading through changing times very quickly.